Réflexions sur le choix du manuscrit de base aujourd’hui ou La précaution inutile ? - Olivier Delsaux; Tania Van Hemelryck (Perspectives Médiévales)
This article will study the role of base-manuscripts in contemporary editions of middle French texts. More specifically, it will consider the value of the external analysis of a manuscript, and assess its editorial relevance. We will focus on the following criteria : technology (manuscript vs printed book), technique, medium, calligraphy, illustration, craftsman, first owner, dedicatee, reader. By doing so, this article will illustrate how auxiliary sciences for book history have influenced the theoretical and practical frames of French philology in the past three decades.